ANALISIS KINERJA BETON DENGAN AGREGAT HALUS PS BALL DI AIR LAUT - Riandika, Muhammad; Mustofa, Amalia; Saputra, Jonathan (Politeknik Negeri Jakarta, 2024)
This study aims to determine the performance of concrete using the residual of steelmaking materials (Precious Slag Ball) as a partial substitution of fine aggregate. In this study, the test object was made with a water–cement ratio of 0.3 and using Precious Slag Ball’s proportions of 0%, 15%, 30% and 45% to the weight of fine aggregate. The test object was then immersed in sea water obtained from the estuary area. The fresh concrete test consists of slump test, initial setting time, and unit weight of fresh concrete. The hardened concrete test consists of unit weight of hardened concrete, compressive strength, and splitting tensile strength. In the 45% Precious Slag Ball variation, the use of Precious Slag Ball in concrete increases the maximum slump workability up to 32.25% and the unit weight value of fresh concrete up to 5.98%. In the setting time test, the fastest setting time is 261 minutes from the 15% Precious Slag Ball variation. In the hardened concrete test, the use of Precious Slag Ball increased the unit weight value of hardened concrete up to 4.94% at a variation of 45% Precious Slag Ball. The greatest value of concrete compressive strength test using 30% of the Precious Slag Ball as a substitution of fine aggregate variation found at the age of 3, 7, 14 and 28 days. The use of Precious Slag Ball is proven able to increase the compressive strength and tensile strength as the concrete tensile strength increases up to 7.12% at a variation of 30% Precious Slag Ball.